2017
DOI: 10.3389/fcimb.2017.00067
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Endosomal Anion/Proton Exchanger ClC-5 Increases Cell Susceptibility toward Clostridium difficile Toxins TcdA and TcdB

Abstract: Virulent C. difficile toxins TcdA and TcdB invade host intestinal epithelia by endocytosis and use the acidic environment of intracellular vesicles for further processing and activation. We investigated the role of ClC-5, a chloride/proton exchanger expressed in the endosomes of gastrointestinal epithelial cells, in the activation and processing of C. difficile toxins. Enhanced intoxication by TcdA and TcdB was observed in cells expressing ClC-5 but not ClC-4, another chloride/proton exchanger with similar fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…EIPA-treated cells completely rounded up, which indicated only reduced uptake instead of complete abolishment, as it can be achieved by bafilomycin A. The role in toxin uptake of the chloride/ proton antiporter ClC-5, which directly acidifies endosomes, was reported before (Ruhe et al, 2017;Smith & Lippiat, 2010). All strategies gave results that were in line with our hypothesis of a Rac1dependent effect mediated by intracellular flush of toxin.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…EIPA-treated cells completely rounded up, which indicated only reduced uptake instead of complete abolishment, as it can be achieved by bafilomycin A. The role in toxin uptake of the chloride/ proton antiporter ClC-5, which directly acidifies endosomes, was reported before (Ruhe et al, 2017;Smith & Lippiat, 2010). All strategies gave results that were in line with our hypothesis of a Rac1dependent effect mediated by intracellular flush of toxin.…”
Section: Discussionsupporting
confidence: 82%
“…This was also proven for TcdB from strain R20291, where even the complete CROP domain except four amino acids was removed (TcdB R20291 1–1836 Figure S4). We recently observed that the ClC‐5 anion/proton exchanger makes cells more susceptible to TcdA and TcdB (Ruhe et al, ). ClC‐5 supports the v‐ATPase in acidification of endosomes and by generating a beneficial electrochemical gradient, thereby accelerating uptake and translocation of toxins (Hara‐Chikuma, Wang, Guggino, Guggino, & Verkman, ; Novarino, Weinert, Rickheit, & Jentsch, ; Piwon, Gunther, Schwake, Bosl, & Jentsch, ; Wang et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake into cells solely by frizzled 1,2,7 does not provoke this effect in HEp‐2 cells as shown in Figure by using TcdB1‐1832, which does not interact with CSPG4 (Henkel et al., 2020; Tao et al., 2016). Beside receptors, facilitation of acidification of the endosomal lumen by sodium and chloride flux also supports toxin translocation, thereby enhancing cytopathic and cytotoxic effects especially of TcdB (Beer et al., 2018a, 2018b; Ruhe et al., 2017). The early cell death can only be executed in the presence of signaling competent Rac1 and NADPH oxidase and is triggered by necrotic calcium signaling (Beer et al., 2018a, 2018b; Farrow et al., 2013, 2020).…”
Section: Discussionmentioning
confidence: 99%